Estudio de las corrientes de fuga en descargadores de sobretensión de los Sistemas Eléctricos de Distribución. - León Chiluiza, Adriana Karina (2023)
This research project is dedicated to the analysis of leakage currents in surge arresters of electrical distribution systems (13.8kV), using current national and international standards such as: IEC 60099-4, IEC 60099-5, NTE INEN 3098, IEEE Std C62.11, ISO 9001, IEE Working group 3.4.11 and MEER. In the first instance, a bibliographical investigation was carried out about the Downloaders of overvoltage, types of overvoltages, leakage currents, etc. Later it was selected the suitable arresters for the electrical distribution system (13.8kV) based on their rated operating voltage, operating current, and discharge class; In addition, it was carried out measurements in the laboratories of the CATIGLATA complex belonging to the EEASA, where. Third harmonic data of the leakage current was obtained in the four selected arresters, the model proposed by the IEEE Working group 3.4.11 was also considered to be analyzed in the ATPDraw 7.2 software and the cause of aging was analyzed. of new surge arresters, used in less than 10 years and used for more than 10 years.